Elementary education in early second millennium BCE Babylonia - Gadotti, Alhena 1972-; Kleinerman, Alexandra (University Park, Pennsylvania Eisenbrauns, 2021)
"Investigates the study of Sumerian by nonnative Akkadian speakers during the Old Babylonian period in areas outside major cities whose schools have been studied extensively. Provides transliterations and translations of 715 cuneiform school exercise texts"--
Includes bibliographical references and index
Keywords: Sumerian language -- Study and teaching (Elementary) -- Iraq -- Babylonia -- Akkadian speakers -- History -- To 1500; Education, Elementary -- Iraq -- Babylonia -- History -- To 1500; Cuneiform tablets -- Iraq -- Babylonia; Sumerian language -- Study and teaching (Elementary) -- Iraq -- Babylonia -- Akkadian speakers -- History -- To 1500; Education, Elementary -- Iraq -- Babylonia -- History -- To 1500; Sumerian language -- Texts; Cuneiform inscriptions, Sumerian -- Translations into English; Cuneiform tablets -- Iraq -- Babylonia; Quelle